(3JWhQ GdfXGe GdeGdj GdLRGFQj (B:s (3OQGSI JMdjdjI (B/s - (3HNhT, djfOIs; (3HdOj, eQhis ((3GdLRGFQ (B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3eSGQ JWhQ GdfXGe GdeUQaj GdLRGFQj aj VhA GdGUdGMGJ, JMdjd JWhQ GdfXGe GdeUQaj(B: (3HYO GdYeb GdeGdj, JMdjd JWhQ GdfXGe GdeUQaj(B: (3HYO GdhUhd (B''(3GdTehd(B''(3, GdcaGAI h GdGSJbQGQ Gdedj, h JMOjGJ EUdGM GdefXheI GdeUQajI HGdLRGFQ, JMdjd JWhQ HhQUI GdLRGFQ s
(3HHdjhYQGajG(B: (3U(B. (3U(B. 236-247s
Keywords: (3GdHhQUGJs; (3GdfXGe GdfbOj(B- (3GdLRGFQs